Biosynthetic Potential-Based Strain Prioritization for Natural Product Discovery: A Showcase for Diterpenoid-Producing Actinomycetes - Xie, Pengfei (American Chemical Society and American Society of Pharmacognosy, 2014)
[Image: see text] Natural products remain the best sources of drugs and drug leads and serve as outstanding small-molecule probes to dissect fundamental biological processes. A great challenge for the natural product community is to discover novel natural products efficiently and cost effectively. Here we report the development of a practical method to survey biosynthetic potential in microorganisms, thereby identifying the most promising strains and prioritizing them for natural product discovery. Central to our approach is the innovative preparation, by a two-tiered PCR method, of a pool of pathway-specific probes, thereby allowing the survey of all variants of the biosynthetic machineries for the targeted class of natural products. The utility of the method was demonstrated by surveying 100 strains, randomly selected from our actinomycete collection, for their biosynthetic potential of four classes of natural products, aromatic polyketides, reduced polyketides, nonribosomal peptides, and diterpenoids, identifying 16 talented strains. One of the talented strains, Streptomyces griseus CB00830, was finally chosen to showcase the discovery of the targeted classes of natural products, resulting in the isolation of three diterpenoids, six nonribosomal peptides and related metabolites, and three polyketides. Variations of this method should be applicable to the discovery of other classes of natural products.